Geophysical modeling of the manganese deposit for Induced Polarization method in Itapira (Brazil) - Vieira, Leandro B. [UNESP]; Moreira, Cesar A. [UNESP]; Cortes, Ariane R. P. [UNESP]; Luvizotto, George L. [UNESP] (Inst Geophysics Unam, 2016)
This paper presents the results of the investigation of a supergene manganese occurrence in the southeast of Brazil, using the Induced Polarization geophysical method. This study aims to characterize the surface and subsurface morphology of one of these occurrences, named Sao Roque, based on the contrast of the electrical properties of the ore and the host rocks. The ore, which is composed mainly of manganese oxides and hydroxides and subordinated graphite, occurs in the form of small discontinuous lenses hosted by quartzites and schists of the Itapira Group. The geophysical survey consisted on 10 lines of Induced Polarization Tomography using a Wenner-Schlumberger array, with an along line electrode separation of 10 m for all lines. The IP data were modeled through commercial inversion software to generate 2D section models of chargeability. In order to create a 3D visualization model of chargeability, the 2D inversion models were then combined and interpolated in order to create a 3D visualization model. The 3D model revealed two independent ore bodies in both surface and subsurface, characterized for high chargeability (up to 20mV/V), instead of a single elongated orebody as suggested by the lateritic surface in the field. In addition, the model showed that the orebodies are elongated perpendicular to the area main structural trend and the regional alignment of the lateritic occurrences, which can bring new ideas in terms of local exploration strategies for manganese in this context.
Keywords: electrical tomographic; lateritic manganese; graphite; chargeability; 3D modeling